ANALISIS EVENT STUDY ATAS KEBIJAKAN TAX AMNESTY (Studi Kasus Sektor Perbankan Yang Tercatat Di Bursa Efek Indonesia) - Zahratul Husna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to determine the reaction of stock price in response to tax amnesty policy, observed from the reaction of abnormal return and trading volume activity of banking stocks listed in the Indonesia Stock Exchange in the period of tax amnesty event. The sample of this study is the stock of twelve banks listed in the Indonesia Stock Exchange, that are selected through purposive sampling technique. This research was conducted using event study method with market model. The period of observation is 401 trading days, which are 200 days prior to, one day during, and 200 days after the event. The statistical test used in this study is one sample t-test, which is used to determine whether significant differences occur on abnormal return and trading volume activity before and after the event. The results show that there is a significant market reaction proxied by abnormal return and trading volume activity around tax amnesty policy event. This is shown by differences on average abnormal return and trading volume activities before and after the event.Keywords: Tax Amnesty, abnormal return, trading volume activity, event study.